Mengkaji Ketandusan Upaya Guru-Guru di Sekolah Menengah Daerah Kota Setar - Jasmani, Mohd. Yunus (2003)
The main focused of this study is to know about burnout that were being experienced by teachers from the district of Kota Setar and the level of their burnout. This study showed that the factor of burnout felt by these teachers is due to environmental factor such as shortage of staffs and facilities, workload and role overload, changes of work place which they dislike and unsupportive administrators that caused fatigue (Faber, 1982; MC Guire, 1979; Shakarof & Farber, 1983). The result of these analysis indicated that there are significant relationship between burnout and workload factors. These factors is also a significant speculative factor which is similar with the workload factor and diminishing of personal accomplishment which are related to burnout. Other than summarization, the statistics results in this study also indicated that there are no significant between both emotional exhaustion and depersonalization level with burnout of teachers in the district of Kota Setar. Nevertheless, the mean levels of emotional exhaustion and depersonalization level of teachers in the district of Kota Setar were significantly slightly higher between each other. These can be explained due to the additional time of interaction between teachers, students and theirs peers in the school systems added to the emotional exhaustion and depersonalization of teachers. Significantly both workload and role overload among teachers in the district of Kota setar are higher based on the analysis of survey’s questions no. S2, S3, Al0 and A11, the average class size in district of Kota Setar are large. Teachers in these school have to spend their time preparing their lesson and finishing their school work at home and at the same time they also have to spend their time in school for their co-curriculum activities. Due to these reasons the level of workload and role overload of Kota Setar’s teachers are significantly higher, thus influences the emotional and depersonalization levels. Questions that were raised in the discussions and suggestions were how far this study’s results showed insignificant relationship between emotional exhaustions and depersonalization with burnout; significant relationship in term of diminishing of personal accomplishment task and role overload with burnout among teachers of the district of Kota Setar. According to Friedman (1991), prestiges school is categorized as high burnout school and normal schools were categorized as low burnout school. The demands from the education department, parents and schools on the teacher roles from prestige’s school are very high. In order to fulfill these demands, the role overload increases. thus increases the level of burnout. Therefore, significant differences in excessive level of burnout among the teachers of the district of Kota Setar were due to the the level of work and demand overload.